Heroic identity and multitude identity in the ’Iliad’ - Oliveira, Gustavo Junqueira Duarte (Romanitas - Revista de Estudos Grecolatinos, 2013)
In the Iliad, the crowd plays a fundamental role in the construction of the poem. It helps to set the story in an epic war stage, besides being necessary to define the poem’s key figures: the heroes. A discussion of the function of the crowd, mass, mob or collectivity is presented, regarding a poem in which the main focus lays in another element. It was necessary to present the manner in which the crowd ensures that the hero is portrayed in an epic fashion. Using the concept of identities, this paper intends to define the manner which these two elements interact in the Iliad. The conclusion is that the crowd sets the stage and defines the hero’s actions, being an essential element to the understanding of the Homeric poem.